2019
DOI: 10.1002/advs.201970053
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning: Deep Learning Spectroscopy: Neural Networks for Molecular Excitation Spectra (Adv. Sci. 9/2019)

Abstract: With artificial intelligence (AI), we learn the relationship between molecular structure and properties. In article number 1801367 , Patrick Rinke and co‐workers build a deep learning AI spectroscopist that can make predictions for molecular spectra instantly and at no further cost for the end user. AI spectroscopy will greatly accelerate the way in which science is done and aid materials discovery and design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Apart from being a useful reference for 2D materials research, our library can be used to train machine learning algorithms for materials science problems . Similarly to recent work on prediction of linear optical spectra for molecules, our database may enable prediction of NLO spectra directly from the atomic structure and, in turn, autonomous ( in situ ) characterization of materials …”
Section: Discussionmentioning
confidence: 99%
“…Apart from being a useful reference for 2D materials research, our library can be used to train machine learning algorithms for materials science problems . Similarly to recent work on prediction of linear optical spectra for molecules, our database may enable prediction of NLO spectra directly from the atomic structure and, in turn, autonomous ( in situ ) characterization of materials …”
Section: Discussionmentioning
confidence: 99%
“…Apart from being a useful reference for 2D materials research, our library can be used to train machine learning algorithms for materials science problems [73]. Similarly to recent work on prediction of linear optical spectra for molecules [74], our database may enable prediction of NLO spectra directly from the atomic structure and, in turn, autonomous (in situ) characterization of materials [75].…”
Section: Discussionmentioning
confidence: 99%
“…The original dataset contained a few very small molecules, such as CH 4 , for which some of the lowest-energy excitations lie far below −30 eV (in the range around −200 eV). 10 We consider 12 such small molecules as outliers and clean the dataset by removing these molecules, leaving 132,519 molecules for our evaluation.…”
Section: ■ Methodsmentioning
confidence: 99%
“…8 Early efforts for the ML-based prediction of molecular spectra have been presented elsewhere, 9 whereby TDDFTcalculated UV spectra were used to train machine learning models. A cornerstone work 10 showed that the usage of deep tensor neural networks (DTNN) 11 leads to new state-of-theart results for the prediction of spectra of the frequently used QM9 dataset of organic molecules. DTNNs are graph neural networks (GNNs) that represent the molecules under study with matrices representing charges and distances.…”
Section: ■ Introductionmentioning
confidence: 99%